The Mugil curema species complex (Pisces, Mugilidae): a new karyotype for the Pacific white mullet mitochondrial lineage - Nirchio, Mauro; Oliveira, Claudio [UNESP]; Siccha-Ramirez, Zoila R. [UNESP]; Sene, Viviani F. de [UNESP]; Sola, Luciana; Milana, Valentina; Rossi, Anna Rita (Pensoft Publ, 2017)
Recent molecular phylogenetic analyses have shown that the Mugil curema Valenciennes, 1836 species complex includes M. incilis Hancock, 1830, M. thoburni (Jordan & Starks, 1896) and at least four M. curema mitochondrial lineages, considered as cryptic species. The cytogenetic data on some representatives of the species complex have shown a high cytogenetic diversity. This research reports the results of cytogenetic and molecular analyses of white mullet collected in Ecuador. The analyzed specimens were molecularly assigned to the Mugil sp. O, the putative cryptic species present in the Pacific Ocean and showed a 2n = 46 karyotype, which is composed of 2 metacentric and 44 subtelocentric/acrocentric chromosomes. This karyotype is different from the one described for M. incilis (2n = 48) and from those of the two western Atlantic lineages Mugil curema (2n = 28), and Mugil margaritae (2n = 24). Data suggest the need for a morphological analysis to assign a species name to this Pacific lineage.
Keywords: Fish; Mugilidae; cytochrome oxidase subunit I; cytotaxonomy; molecular systematics